Mekambare As a Former of Social Solidarity in Supporting Food Security in Sustainable Agriculture Management in East Kolaka Regency - La Ode Topo Jers; Efriani Efriani; Yevita Nurti; Putu Arimbawa; Alias Alias (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
The local community’s culture has been recognized as playing an essential role in achieving food security. This study attempts to demystify a cultural tradition among an Indonesian agriculture society, called Mekambare, that plays such a role in sustainable agricultural management. It was conducted in East Kolaka Regency, an area dominated by lowland rice farmers. Framed in a qualitative method, this study used observation, in-depth interviews, and document studies as techniques of data collection. The results showed that Mekambare played a crucial role in forming social solidarity among lowland rice farming communities. Through Mekambare, farming communities build mutual cooperation and support one another in overcoming challenges related to supplying food demands. This social solidarity is manifested in the exchange of food commodities, social support, and the dissemination of traditional knowledge in agricultural management. With Mekambare, the lowland rice farming communities maintain the balance of the agricultural ecosystem by utilizing natural predators, utilizing organic fertilizers from livestock manure, and implementing integrated weed control. This research can make a positive contribution to efforts to achieve sustainable food security and the welfare of farming communities in East Kolaka Regency.